ANALISIS EFEKTIVITAS PENERAPAN TAPPING BOX SEBAGAI MONITORING PAJAK DAERAH (STUDI PAJAK RESTORAN, HOTEL, HIBURAN, DAN PARKIR) - Rafika, Latifah; Limarjani, Sustinah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
This study was conducted with the intention of learning more about and analyzing the benefits of implementing the tapping box policy, the limitations that exist in the use of the regional tax tapping box for Banjarbaru City, as well as the efforts made to get around these barriers. It also had the goal of learning more about and analyzing the effectiveness of the application of tapping boxes as regional tax monitoring. The focus of this research is on four local taxes in Banjarbaru City the restaurant, hotel, entertainment, and parking taxes all of which have already adopted the usage of tapping tool boxes, totaling 79 taxpayers in the city. Both primary and secondary data sources were utilised in this study's data collection. The appropriate policy, the right implementer, the right goal, the right environment, and the right procedure are the five criteria that must be met for a policy to be considered successful in the data analysis approach. The study's findings indicated that the tapping box policy application as a means of monitoring local taxes may be regarded as successful since it already satisfies all five requirements for a policy to be deemed effective.